2022
DOI: 10.3390/nu14204228
|View full text |Cite
|
Sign up to set email alerts
|

Food Outlet Access and the Healthiness of Food Available ‘On-Demand’ via Meal Delivery Apps in New Zealand

Abstract: Access to unhealthy commodities is a key factor determining consumption, and therefore influences the prevalence of non-communicable diseases. Recently, there has been an increase in the availability of food ‘on-demand’ via meal delivery apps (MDAs). However, the public health and equity impacts of this shift are not yet well understood. This study focused on three MDAs in New Zealand and aimed to answer (1) what is the health profile of the foods being offered on-demand, (2) how many food outlets are availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Nine of these studies examined the characteristics of online food delivery platform users, with the remaining 13 studies examining the characteristics of the platforms themselves, such as the in‐app promotional marketing, the healthiness of products offered, and their food availability across different geographical areas 68,69,71,73–77,80,82,83,86,87 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine of these studies examined the characteristics of online food delivery platform users, with the remaining 13 studies examining the characteristics of the platforms themselves, such as the in‐app promotional marketing, the healthiness of products offered, and their food availability across different geographical areas 68,69,71,73–77,80,82,83,86,87 …”
Section: Resultsmentioning
confidence: 99%
“…Nine of these studies examined the characteristics of online food delivery platform users, with the remaining 13 studies examining the characteristics of the platforms themselves, such as the in-app promotional marketing, the healthiness of products offered, and their food availability across different geographical areas. 68,69,71,[73][74][75][76][77]80,82,83,86,87 The studies that examined the users of online food delivery platforms were based in the United Kingdom, 79,81 Australia, 70,84 Malaysia, 72 Saudi Arabia, 67 Singapore, 85 the United States, 40 and multiple high income countries. 78 Two studies examined the influence of online food delivery platforms on dietary habits during COVID-19 lockdown restrictions, 67,85 one study examined the in-app advertising of online food delivery platforms during the COVID-19 pandemic, 75 and one study examined what food items were promoted on online food delivery platforms during the COVID-19 pandemic.…”
Section: Online Food Delivery Platformsmentioning
confidence: 99%
“…We also sampled to ensure that one‐third of addresses were areas within the top 20th percentile of Māori within each city. The stratified sampling method enabled evaluation of each variable in isolation of the others, similar to the approach taken previously for a study of on‐demand food access [18]. The density of physical alcohol outlets [19] was substituted for the density of unhealthy food outlets from a prior study.…”
Section: Methodsmentioning
confidence: 99%
“…T A B L E 2 Summary measures of access to on-demand alcohol. access [18]. The density of physical alcohol outlets [19] was substituted for the density of unhealthy food outlets from a prior study.…”
Section: Count Of Available Alcohol Vendorsmentioning
confidence: 99%
“…This form of food delivery has gained popularity, especially during the COVID-19 pandemic. A recent study looking at the healthiness of food and menu items in three cities in in New Zealand showed that over 75% of food and menu items offered on MDAs were classified as unhealthy based on Eating and Activity Guidelines for New Zealand Adults [ 14 ]. This trend has been observed in previous studies [ 15 , 16 , 17 ].…”
Section: Digital Food Environments and Public Healthmentioning
confidence: 99%